2005
DOI: 10.1016/j.vaccine.2004.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal immunization with inactivated SARS-CoV (SARS-associated coronavirus) induced local and serum antibodies in mice

Abstract: SARS-CoV (severe acute respiratory syndrome-associated coronavirus) strain GZ50 was partially purified and inactivated with 1:2000 formaldehyde. In cell culture the inactivated virus blocked the replication of live virus by decreasing the TCID(5.0) of the live virus 10(3.6) to 10(4.6) times. Inactivated GZ50 was used to immunize mice intranasally either alone, or after precipitation with polyethylene glycol (PEG), or with CpG, or CTB as an adjuvant. The titer of serum neutralizing antibodies was up to 1:640. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 24 publications
1
62
1
2
Order By: Relevance
“…When SARS-CoV is treated with 0.05% formaldehyde for 48 h, it could be inactivated properly [31]. Vaccines based on formaldehyde-inactivated SARS-CoV are shown to induce virus-specific and virus-neutralizing antibodies [32,33]; however, some virus still remained infectious on day 3 of inactivation [30].…”
Section: Reviewmentioning
confidence: 99%
“…When SARS-CoV is treated with 0.05% formaldehyde for 48 h, it could be inactivated properly [31]. Vaccines based on formaldehyde-inactivated SARS-CoV are shown to induce virus-specific and virus-neutralizing antibodies [32,33]; however, some virus still remained infectious on day 3 of inactivation [30].…”
Section: Reviewmentioning
confidence: 99%
“…and i.n. routes, following the protocols described previously with some modifications (42)(43)(44). For the i.m.…”
Section: Mice Vaccination Via Im and In Routes And Sample Collectionmentioning
confidence: 99%
“…However, once the neutralizing epitopes are identified, the inactivated virus vaccine should be replaced by vaccines based on fragments containing neutralizing epitopes since they are safer and more effective. Several reports have showed that SARS-CoV inactivated with formaldehyde, UV light, and β-propiolactone can induce virus-neutralizing antibodies in immunized animals (8)(9)(10)(11), and the first inactivated SARS-CoV vaccine is being tested in the clinical trials in China. However, safety of the inactivated vaccine is a serious concern; production workers are at risk for infection during handling of concentrated live SARS-CoV, incomplete virus inactivation may cause SARS outbreaks among the vaccinated populations, and some viral proteins may induce harmful immune or inflammatory responses, even causing SARS-like diseases (12,13).…”
Section: Inactivated Sars-cov-based Vaccinesmentioning
confidence: 99%